Vasudeva hands over the infant Krishna to Nanda - Mahabharata - 51 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in Vasudeva carries baby Krishna, who is protected by Adisesa, across the Yamuna river and hands him over to Yashoda. The river is artfully depicted with tortoises and fishes inside it.